The Correlation between Fetuin-A Levels And Nafld Fibrosis Score (NFS) - Hafiz Syaifullah Siregar (Talenta Publisher, 2022)
Abstract. Fetuin-A is a plasma glycoprotein expressed in the liver. Fatty liver accumulation because changing fetuin-A expression leads to nonalcoholic fatty liver disease (NAFLD). The benefits of serum fetuin-A as a predictor of fibrosis biomarkers in NAFLD patients remain unclear. Non-invasive scoring system predicting fibrosis among patients with NAFLD is the NAFLD fibrosis score (NFS). Objective. This study aims to find the correlation between circulating fetuin-A levels and NFS in NAFLD patients. Methods. Eighty subjects (male, 52; female, 26) followed this cross-sectional study. NAFLD is diagnosed with an abdominal ultrasound. The serum levels of fetuin-A measured by ELISA. NFS is used to identify the probability of fibrosis in subjects. The correlation between Fetuin-A levels and NFS was determined using Pearson correlation tests. A p-value < 0.05 was significant. Results. There was significant difference in fetuin-A levels (p < 0.001) between NAFLD degree I (421.71 pg/mL), NAFLD degree II (494.88 pg/mL), and NAFLD degree III (692 pg/mL). The NFS low probability score in 46 subjects and NFS indeterminate score in 34 subjects. Serum concentrations of fetuin-A correlate significantly with NFS (r = 0.478, p < 0.001). Conclusion. There is a positive correlation between serum levels of fetuin-A and NFS.